Analisis Mitigasi Risiko Pada Pembiayaan Mudharabah di PT. Bank Syariah Mandiri - Sofiyyatul Huda; Fajri Ryan Isnandar (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2020)
Mudharabah financing is a form of cooperation between two or more parties, in which the ownerof the capital (shahibul maal) entrusts a certain amount of capital to the manager (mudharib) to bemanaged with a profit-sharing agreement (profit sharing). This study aims to determine what risksarise in mudharabah financing and how risk mitigation is carried out by Bank Syariah Mandiri. Thisresearch is research using descriptive qualitative method. Data were collected through observation,interviews with the FGD (Focus Group Discussion) method with 4 (four) sources and documentation.The method of data analysis was done by using the descriptive analysis method.. The results show thatthe risks that arise in mudharabah financing at Bank Syariah Mandiri are: First, the risk of financingcaused by the customer not being able to pay their obligations to the bank, and second, the legalrisk caused by the weakness of the agreement (agreement). As for the mitigation carried out by BankSyariah Mandiri in dealing with risks that arise in mudharabah financing, namely: First, by rigorouslyconducting 5C and 6A analysis. Second, by taking steps to save financing, including (1) intensivecollection, (2) giving warnings, (3) rescheduling, (4) reconditioning, (5) restructuring, (6) settlementthrough guarantee insurance, (7) Settlement through guarantees, (8) Settlement through Write Off,(9) Settlement through stipulation of fines / ta’wid. From risk mitigation carried out by Bank SyariahMandiri, it has been able to minimize the risks that occur in mudharabah financing.